"COLORS IN PAINTING" (IN PERSPECTIVE FROM PREHISTORIC TIMES TO PRESENT TIMES): ‘‘चित्रकला में रंग’’ (प्रागैतिहासिक काल से वर्तमान काल तक के परिपेक्ष्य में) - Tripathi, Surabhi (International Journal of Research -GRANTHAALAYAH, 2014)
Color is synonymous with happiness, sorrow, excitement, fear, relaxation, joy, etc. Color permeates nature's particles. Each color of a ghara has its own aesthetic and natural qualities, but how to apply it depends on the skill and efficiency of the artist, in a way the colors are the expression of human tendency, which the artist with his experience Presents. Man's attraction towards colors is not only natural but also inborn, thus color is the most important and meaningful element of a person's artwork. Color is also an expression of a person. Varna (color) has its own special importance in Hinduism - Gore class was used for Brahmin, Red color for Kshatriya, Yellow-vest and Shyam varna (black) for Sudra. Which is called varna bheda in Hinduism, thus color expresses natural expressions that are different from amukh, which creates a distinction in the object which becomes its existence. There is also a color attitude, which has its own natural quality. Colors directly affect our psyche. For this purpose, the treatment of 'color therapy' is also taken, for which various patients are freed. Physicians and psychologists are involved in this process. सुख-दुःख, उत्तेजना, भय, विश्राम, उल्लास आदि का पर्याय ही रंग है। रंग प्रकृति के कण-कण में व्याप्त है। घरा के प्रत्येक रंग का अपना एक सौदंर्य व नैसर्गिक गुण होता है, परन्तु उसे किस प्रकार प्रयुक्त किया जाय यह कलाकार की कुशलता एवं दक्षता पर निर्भर करता है, एक प्रकार से रंग ही मनुष्य की प्रवृत्ति की अभिव्यक्ति हैं, जिसे कलाकार अपने अनुभव के साथ प्रस्तुत करता है। रंगों के प्रति मनुष्य का आकर्षण स्वाभाविक ही नहीं वरन् जन्मजात है, इस प्रकार रंग व्यक्ति विशेष की कलाकृति का सबसे महत्वपूर्ण व सार्थक तत्व है। रंग व्यक्ति विशेष की अभिव्यक्ति भी है। हिन्दू धर्म में वर्ण (रंग) का अपना विशेष महत्व है- गोर वर्ग ब्राह्मण, लाल वर्ण क्षत्रीय के लिए, पीला-वेश्य तथा श्याम वर्ण (काला) सूद्र के लिए प्रयुक्त किया गया। जिसे हिन्दू धर्म में वर्ण भेद कहा गया है इस प्रकार रंग प्राकृतिक भाव-भंगिमाओं को व्यक्त करता है जो अमुख से भिन्न है, जो वस्तु में भेद पैदा करता है जो उसका अस्तित्व बन जाती है। रंग मनोवृत्ति भी है, जिसका अपना स्वाभाविक गुण होता है। रंग हमारे मनोविकारों को सीधे प्रभावित करते हैं। इसी निमित्त रोग-निदान के लिए ‘कलर थेरपी’ का सहारा भी लिया जाता है, जिससे विभिन्न रोगियों को रोगमुक्त किया जाता है। इस प्रक्रिया के चिकित्सक-मनोवैज्ञानिक होते है।